The purge of mortgage in Japanese civil law - ZHANG, Wei (Institutional Knowledge at Singapore Management University, 2002)
The purge of mortgage is believed to be one of the few French remnants in the otherwise largely German style Japanese Civil Code. Since the breakdown of Japanese asset price bubble in early 1990s, it has been blamed as one major obstacle to clearing up nonperforming loans held by Japanese banks, and a central target subject to abolishment. In this paper, I analyzed the structural problems existing in the Japanese purge system and also probed the history and social background behind the debates about its abolishment. I proposed that, instead of total abolition, a restructured purge system, in particular getting rid of the requirement of increased-price-auction, can still serve certain important purposes of real estate development and finance in today’s Japanese society. In addition, I pointed out that a transformed purge system will also be useful in solving the dilemma faced by current Chinese residential property development market where buildings sold uncompleted, subject to mortgages held by banks, bring substantial title risks to their purchasers.